Electrochemical capacitive biosensors for point-of-care diagnostics: Principles and applications - Bueno, Paulo R. [UNESP] (Institution of Engineering and Technology (IET), 2016)
Before introducing the concepts involved in using capacitance measurements as an approach to transducer biological event into a measurable electrical signal, through electrochemistry interfaces, we will shortly make reference to the concepts employed on potentiometric including Field Effect Transistor (FET) electrochemical based methods such as ion-sensitive [27] FETs, amperometric and impedimetric biosensor devices, since they are massively used in electrochemistry biosensor applications as can be observed in specialized literature. This will thus facilitate further comparisons and will help us to classify the electrochemical capacitive biosensors regarding its advantages and/or disadvantages in terms of their potential applications. Finally, we would like to mention that additional measurement techniques, which have been shown useful performance in combination with electrochemical detection, are out of the scope of this chapter, even in terms of conceptual comparisons, such as the electrochemical versions of surface plasmon resonance, optical waveguide light-mode spectroscopy, ellipsometry, quartz crystal microbalance and scanning electrochemical microscopy. Various types of transducers have been shown in Figure 15.3.
Keywords: Amperometric biosensor; Biosensors; Capacitance measurements; Capacitive sensors; Electrochemical capacitive biosensors; Electrochemical detection; Electrochemical sensors; Electrochemistry interfaces; Ellipsometry; Field effect transistor; Field effect transistors; Impedimetric biosensor; Optical waveguide light mode spectroscopy; Patient diagnosis; Point-of-care diagnostics; Quartz crystal microbalance; Quartz crystal microbalances; Scanning electrochemical microscopy; Surface plasmon resonance